Evaluation of Antitumor, Antioxidant and Antibacterial Activities of the Extracts of Saussurea atkinsonii - Shahwar, Durre; Ullah, Sami; Altaf, Imran; Ahmad, Naeem; Ullah, Saif; Akmal Khan, Muhammad; Saeed, Afifa (Asian Journal of Chemistry, 2011)
The Saussurea atkinsonii, a member of family Asteraceae is abundant in the northern areas of Pakistan, traditionally used for the treatment of variety of diseases. The whole plant of S. atkinsonii was extracted in hexane, chloroform and methanol by using sohxlet. Antioxidant activity was determined by DPPH, total antioxidant, TBA, FTC and TLC autobiography. Six bacterial strains were used for the evaluation of antibacterial activity. The antitumor activity of the extracts was checked against the BHK-21 cell line. MTT colorimetric assay was used to evaluate the reduction of viability of cell cultures in the presence and absence of the extracts. The 50 % inhibitory concentration (IC50) for each extract was calculated by linear regression analysis and maximum antitumor activity was observed for methanol extract of S. atkinsonii with IC50 value 1.19 × 10-2 after the incubation period of 72 h.